the Pengaruh Faktor Ibu dan Budaya Kerja Berat Saat Hamil Terhadap Kejadian BBLR di Kota Kupang - aysanti yuliana paulus (STIKes CHMK, 2019)
Low Birth Weight (LBW) is still considered a big problem in the world, especially in developing countries. LBW is a major indicator for reproductive health and public health status in general. LBW is also one of the main causes of neonatal illness and death. East Nusa Tenggara Province still has a high Infant Mortality Rate, which is higher than the national level. In 2012 IMR in East Nusa Tenggara was 45 per 1000 live births. LBW cases may incur death and therefore require special treatment. Long term effects on babies with LBW among others are psychological problems such as speaking disorder, growth and development disorder, learning disabilities, and physical problems e.g. chronic pneumonia and inherited disorders. This is analitic research with case control design. Population in this study were all mothers in Kupang City. Through accidental sampling technique, 100 people were selected, consisting of 50 mothers who had LBW infants and 50 mothers who had normal infants. Univariate and bivariate analysis on data were conducted using chi-square whereas multivariate test using multiple logistic regression test. The result show that Maternal factors were proven to have an effect on the occurrence of LBW i.e. maternal age factor during pregnancy (p: 0,041, OR: 3,606; CI: 1,894-14,528), suffering from ilness during pregnancy (p: 0,049; OR: 3,072; CI: 1,841-11,215 ), mother education is a protective factor (p: 0,007; OR: 0,241; CI: 0,085-0,682). The hard working culture during pregnancy is also a factor affecting LBW (p: 0.008; OR: 4,467; CI: 1,476-13,518). So, At risk age (<20 years and> 35 years), good education, history of illness during pregnancy, and conducting hard work during pregnancy have the 56,12%.probability of giving birth to LBW infants. Keywords: LBW, Maternal Factors, Hard Working During Pregnancy Culture.